2017
DOI: 10.20344/amp.8029
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Weekend and Holiday Admission with Pneumonia and Mortality in a Tertiary Center in Portugal: A Cross-Sectional Study

Abstract: Little is known about this effect in patients with acute bacterial pneumonia.Objective: The aim of this study was to evaluate the impact of weekend and holiday hospital admission on the outcomes of acute bacterial pneumonia. Material and Methods:Retrospective analysis of adult patients (> 18 years) with acute bacterial pneumonia collected from a tertiary referral center database. Length of stay, total cost, admission to intensive care unit, development of sepsis and organ failure, and mortality were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Few studies have evaluated the association of diagnosing infectious diseases and sepsis at different periods of the day and the week on compliance with guidelines and outcomes, and the results have been conflicting (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the association of diagnosing infectious diseases and sepsis at different periods of the day and the week on compliance with guidelines and outcomes, and the results have been conflicting (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested a reduction in medical staffing and resources as well as a possible restriction in diagnostic and therapeutic tools on weekends to be responsible for the observed differences in mortality and morbidity [ 2 , 3 ]. While studies have shown a weekend effect for different medical conditions (including acute kidney injury [ 4 ], pneumonia [ 5 ] or dysrhythmia [ 6 ]) major commonalities among conditions affected by a weekend effect are the need for time sensitive interventions and care at an intensive care unit. In line with this, there are numerous reports about a weekend effect for stroke [ 7 9 ] myocardial infarction [ 10 , 11 ] or pulmonary embolism [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that patients hospitalized outside regular working hours with myocardial infarction, 1 pulmonary embolism, 2 stroke, 3 ruptured abdominal aortic aneurysm, 4 heart failure, 5 or gastrointestinal bleeding 6 have worse outcomes, but there are few conflicting reports. 7-10 Except for emergency surgical procedures, most complex surgical procedures are done electively. However, when such surgeries are performed at night, a higher incidence of serious complication rates has been reported with colorectal, laparoscopic, and orthopedic surgeries.…”
mentioning
confidence: 99%